Optimalisasi Pengelolaan Bank Sampah Sebagai Upaya Partisipasi Masyarakat Studi Kasus Pengelola Bank Sampah di Desa Mengwi Badung - I Gusti Ayu Lia Yasmita; Ni Made Taman Ayuk; Ni Rai Artini; Ngurah Made Novianha Pynatih; Ni Luh Laksmi Rahmantari; Agus Putra Mardika; I Putu Dharmawan Suryagita Susila Putra (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
This community service aims to optimize bank management in Mengwi Village, Mengwi Regency in an effort to increase efficiency, effectiveness and positive impacts from the existence of waste banks in waste management, which steps will provide efforts for community empowerment and participation. The implementation method used in this service is training, mentoring and evaluation by delivering material directly to the Waste Bank manager in Mengwi Village which is also used as an object of service.The problem faced during the survey was how to raise awareness and involvement of the community to take an active role in the waste bank program. It is hoped that this training and mentoring activity will provide management with education and understanding to the community so that they can work together to maximize the contribution of the waste bank in an effort to manage waste from origin using the 3 R (Reduce, Reuse, Recycle), which ultimately aims to reduce the volume of waste entering the waste bank. landfill, increasing environmental awareness and impacting community welfare. The response from the Mengwi Village Waste Bank management to this activity was very good and positive, this can be seen from the management's willingness to participate in the activity from start to finish. From the evaluation activities carried out on waste bank managers, it can be said that managers understand the material regarding the importance of providing understanding to the community to participate in developing waste banks. Where in their involvement, the community not only gets a healthy environment, but from an economic perspective, the community also gets benefits by having savings on tires. The savings can later be exchanged for basic necessities such as rice, sugar and coffee.